PENGARUH PENAMBAHAN PENYINARAN DAN APLIKASI INDUKSI SIPLO TERHADAP PERTUMBUHAN DAN HASIL PRODUKSI TANAMAN SELADA KERITING (Lactuca sativa L.) PADA SISTEM HIDROPONIK - Ekka Rizki (AGRONISMA, 2022)
Along with the increasing population in Indonesia, people are starting to realize the need for balanced nutrition for health so that there is an increase in demand for lettuce. The survey results show hydroponic lettuce production by farmers in Kalirejo Village, Kec. Lawang Kab. Malang is still not sufficient for market needs. With a solution using irradiation technology and siplo induction, it can accelerate the growth of hydroponic lettuce. The purpose of this study was to determine the effect of the combination of addition of irradiation and induction of Siplo on lettuce. This study used a Factorial Randomized Block Design (RAKF) with Factor 1 Lighting (P) for 4 hours/day and 8 hours/day, and Factor 2 Induction of SIPLO (S) 1,2, and 3 times/day. The results showed that the best results were irradiation 8 hours/day (P2) and giving SIPLO 3 times (S3) to increase growth and yield. The addition of irradiation and siplo application was effective in increasing the productivity of curly lettuce in the rainy season, the treatment applied resulted in fresh weight. maximum plant.